Analysis of Transmission Loss and Boresight Error of a Curved FSS Radome-Enclosed Antenna - Shin, Hokeun; Yoon, Daeyeong; Na, Dong Yeop; Park, Yong Bae (IEEE Access, 2021)
In this paper, we numerically study a curved frequency selective surface (FSS) radome, which encloses a waveguide slot array antenna operating at 10GHz, using the ray tracing technique and flat model. The transmission loss (TL) and boresight error (BSE) are calculated for various degrees of freedom, such as elevation and azimuth angular scanning or gimbal systems of array antennas to examine the electromagnetic properties of the curved FSS radome. Our calculations of radiation patterns, TL, and BSE for a multi-layered dielectric radome are compared with those of a commercial EM solver for validation. Importantly, we quantify phase distortions, incurred by the curved FSS radome, using the insertion phase delay (IPD) of transmitted fields on the radome surface. Thereby, we demonstrate that the BSEs strongly depend on (1) the spatial distribution of phase distortions on the radome surface and (2) their average level. The present method is highly suited for analyzing radomes with arbitrary surface patterns inserted.
Keywords: Arbitrary surfaces; Electromagnetic properties; Frequency selective surface (FSS); Insertion phase delay; Phase distortions; Ray-tracing technique; Transmission loss; Waveguide slot array antennas; boresight error (BSE); Frequency selective surface (FSS); FSS radome; insertion phase delay (IPD); phase distortion; ray tracing technique